2017
DOI: 10.5114/biolsport.2017.63731
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3 R577X genotype and performance of elite middle-long distance swimmers in China

Abstract: The ACTN3 gene is one of the genes that have a potential influence on physical performance. Studies have shown that the 577R genotype of ACTN3 is more prevalent in sprint athletes, while the 577X genotype is more prevalent in endurance athletes. In swimming, both power and endurance related phenotypes are equally needed for swimmers to excel at the elite level. Therefore, the ACTN3 R577X polymorphism may become a genetic marker for swimmers. The study aimed to examine the association of the ACTN3 R577X genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
10
0
3
Order By: Relevance
“…The results of the four studies that examined only individual disciplines or sports are as follows: Falahati and Arazi could not link any of the genotypes of the ACE variant to the cardiovascular fitness of Iranian footballers (Falahati and Arazi, 2019 ). Ginszt et al ( 2018 ) and Li et al ( 2017 ) investigated the ACTN3 R577X polymorphism in climbing, bouldering, and swimming and both found an overrepresentation of the RR genotype of the gene variant in their groups of athletes. Kikuchi et al ( 2017 ) also found the MCT1 T1470A rs1049434 polymorphism significantly higher in Japanese elite wrestlers and correlated it with their performance in two anaerobic tests.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the four studies that examined only individual disciplines or sports are as follows: Falahati and Arazi could not link any of the genotypes of the ACE variant to the cardiovascular fitness of Iranian footballers (Falahati and Arazi, 2019 ). Ginszt et al ( 2018 ) and Li et al ( 2017 ) investigated the ACTN3 R577X polymorphism in climbing, bouldering, and swimming and both found an overrepresentation of the RR genotype of the gene variant in their groups of athletes. Kikuchi et al ( 2017 ) also found the MCT1 T1470A rs1049434 polymorphism significantly higher in Japanese elite wrestlers and correlated it with their performance in two anaerobic tests.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, this genotype was detected significantly more frequently in sprint and strength athletes and could be associated with their jumping performance. Li et al referred to both strength and endurance-related phenotypes in swimmers (Li et al, 2017 ). The results of their study showed that both the RR genotype and the RX+XX genotype of the ACTN3 polymorphism are significantly overrepresented in these athletes compared to a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates an enhanced capacity for fat/carbohydrate oxidation during repeated and moderate-intensity muscle contractions (Table 2). However, in humans, the potential advantage of the X allele or the XX genotype for endurance sports performance is less clear, with some investigations reporting no increased frequency of the XX genotype in endurance athletes (Grealy et al 2013;Guilherme et al 2018;Papadimitriou et al 2018;Ma et al 2013;Lucia et al 2006;Saunders et al 2007;Yang et al 2007) or even an under-representation of this genotype (Ahmetov et al 2010;Kikuchi et al 2016;Li et al 2017) respect to control/untrained populations. Thus, it can be assumed that perhaps lack of α-actinin-3 does not offer a major advantage for endurance performance, at least in athletic populations (Table 1).…”
Section: Performancementioning
confidence: 99%
“…In this sense, using genetic models, Papadimitriou et al (Papadimitriou et al, 2016) established that the ACTN3 R allele and ACE D allele dominant model account for 0.92 % and 1.48 % of sprint time variance, respectively, in a large, performance-homogenous cohort of elite Australian, Brazilian, Greek, Jamaican, Italian, Polish, Russian, Lithuanian, Spanish and US sprinters. Although some research have established that the genetic background of ACTN3 R577X and/or ACE I/D polymorphisms play an important role in sporting potential, which might explain why some individuals may be better adapted to specific physical training or performance (Chiu et al, 2019;Coelho et al, 2018;Del Coso et al, 2019;Kikuchi et al, 2015;Li et al, 2017;Massidda et al, 2019;R. Yang et al, 2017;Znazen et al, 2015), readers should note that other studies have reported no association between the ACTN3 R577X and/or ACE I/D polymorphism and athletic performance (Falahati & Arazi, 2019;Koku et al, 2019;Maciejewska-Skrendo, Cięszczyk, Chycki, Sawczuk, & Smółka, 2019;Massidda et al, 2015;Miyamoto, Miyamoto-Mikami, Hirata, Kimura, & Fuku, 2018;Moreno-Pérez, Machar, Sanz-Rivas, & Del Coso, 2020;Papadimitriou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%